Groundwater modelling using an analytic element method and finite difference method: An insight into Lower Ganga river basin - Omar P.J.; Gaur S.; Dwivedi S.B.; Dikshit P.K.S. (My University, 2025)
Groundwater flow modelling provides the water flow dynamics for the estimation and prediction of groundwater movement and its condition in the aquifer. The modelling helps for the management of the groundwater resources under various hydrological and anthropogenic stresses. In this paper, a modelling exercise was performed using the analytic element method (AEM) and finite difference method (FDM) for the part of Ganga river basin which includes the Varanasi district. Further compression was performed to understand the limitations and benefits of both AEM and FDM based on ease of model development, data requirement and their performances. The groundwater model was developed for the transient state condition based on data for the year 2004–2017. The results show that for most of the observed wells, the difference between the observed head and the simulated head is found in the 90% confidence level. It is found that the AEM does not require a fixed boundary condition which makes the development of the conceptual model less complicated. In the FDM, pumping wells are approximately located and averaged over the cell which becomes a cause of the inaccurate location of the wells. It is found that model development in the AEM is less complicated compared to the FDM. It can be concluded that in some cases AEM-based modelling is more accurate as compared to FDM-based flow modelling. This study can be very helpful for groundwater professionals in deciding the best suitable method for their study area and to avoid the complexity of the model. © 2019, Indian Academy of Sciences.